DAMPAK POSTINGAN MEDIA JURNALISME WARGA BERBASIS SOSIAL KEMASYARAKATAN TERHADAP TINGKAT KEWASPADAAN PENGIKUT - Cicilia Afrilia Damayanti Simbolon; Chontina Siahaan (Ilmu Komunikasi, FISIP Universitas Pasundan, 2025)
This study was conducted with the aim of finding out whether the presence of posts on the citizen journalism account @infodepok_id has an impact on its followers to remain alert to events or incidents reported on the account. This study uses a quantitative approach with a survey method in the form of a questionnaire. The sample of this study was 100 respondents who were followers of the @infodepok_id account and lived in the Depok area. The results of this study indicate that there is an impact felt by its followers after seeing posts in the form of photos or videos on the account. This is evidenced by several tests conducted with the help of SPSS. One of them is the determination coefficient test which shows the percentage of the impact of account posts on alertness of 43.3%. Then, the results of the T test which show the calculated t results obtained are greater than the specified t table, namely 8,667> 1,985. As well as the results of the Pearson correlation test which shows a strong relationship between variable x, namely posts and variable y, namely alertness, of 0.659.